Cost-Effectiveness Analysis of Gastritis Treatment for Inpatient Patients in Sumedang Regency Hospital - Ramadan, Erlangga; Pandapotan, Fadli Afit; Suwantika, Auliya Abdurrohim (Farmaka, 2023)
Gastritis is a disease caused by inflammation in the stomach. Gastritis is one of the most common diseases in Indonesia, including in Sumedang Hospital. Treatment used in gastritis patients usually consists of H2 receptor antagonists, proton pump inhibitors (PPIs), and antacids. Administration and selection of therapy in the treatment of gastritis given to patients has an impact on the amount of treatment costs. This study aims to analyze the value of cost-effectiveness between the use of omeprazole and lansoprazole in hospitalized gastritis patients at the Sumedang District General Hospital. This study used the Cost-Effectiveness Analysis Method with a retrospective data collection design for the period October 2020 – October 2021. The data collected included patient age, gender, medical costs, treatment costs, laboratory costs and duration of patient hospitalization. The effectiveness value in this study was measured in the length of treatment duration.